The Impact of Organizational Culture, Business Management, and Motivation on the Performance of MSMEs in the Culinary Sector in Pekanbaru City During the Covid-19 Period - Harahap, Kurniati; Machasin, Machasin; Fitri, Kurniawaty (CV. Rayyan Dwi Bharata, 2024)
The reason for this study is to find out how business the board, hierarchical culture, and inspiration impacted the exhibition of Miniature, Little, and Medium-Sized Endeavors (MSME) in Pekanbaru City's culinary area during the Coronavirus flare-up. The population of this study is made up of 209 Micro, Small, and Medium-Sized Businesses located in the city of Pekanbaru.68 These Micro, Small, and Medium-Sized Businesses were chosen as the sample for this study by applying the Slovin formula. Primary data were gathered through the use of a questionnaire to support the findings of the study. The analytical methods used are descriptive analysis, multiple linear regression analysis, and the classical assumption test. We tested the hypothesis and evaluated the instrument's quality by employing the F test (simultaneous test), the t test (partial test), and the analysis of the coefficient of determination (R Square) in SPSS (Statistical Program Society Science) version 25 for Windows. The results showed that the business management variable had a positive and significant impact on the performance of Micro, Small, and Medium-Sized Businesses, that the organizational culture variable had a positive and significant impact on the performance of Micro, Small, and Medium-Sized Businesses, that the motivation variable had a positive and significant impact on the performance of Micro, Small, and Medium-Sized Businesses, and that the business management variables, organizational culture, and motivation had a positive and significant impact simultaneously on the performance of Micro, Small, and Medium Businesses that are Micro, Small, and Medium-Sized Enterprises (MSMEs) must acquire business capital by acquiring additional partners in order to expand.